Fuzzy computing in data science applications and challenges - Mohanty, Sachi Nandan; Chatterjee, Prasenjit; Hung, Bui Thanh (John Wiley & Sons, Inc., 2023)
FUZZY COMPUTING IN DATA SCIENCE This book comprehensively explains how to use various fuzzy-based models to solve real-time industrial challenges. The book provides information about fundamental aspects of the field and explores the myriad applications of fuzzy logic techniques and methods. It presents basic conceptual considerations and case studies of applications of fuzzy computation. It covers the fundamental concepts and techniques for system modeling, information processing, intelligent system design, decision analysis, statistical analysis, pattern recognition, automated learning, system control, and identification. The book also discusses the combination of fuzzy computation techniques with other computational intelligence approaches such as neural and evolutionary computation. Audience Researchers and students in computer science, artificial intelligence, machine learning, big data analytics, and information and communication technology.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on November 16, 2022)
Keywords: Fuzzy logic; Fuzzy systems; Data mining; Logique floue; Systèmes flous; Exploration de données (Informatique)